1997
DOI: 10.1146/annurev.astro.35.1.101
|View full text |Cite
|
Sign up to set email alerts
|

Observational Selection Bias Affecting the Determination of the Extragalactic Distance Scale

Abstract: The influence of Malmquist bias on the studies of extragalactic distances is reviewed, with brief glimpses of the history from Kapteyn to Scott. Special attention is paid to two kinds of biases, for which the names Malmquist biases of the first and second kind are proposed. The essence of these biases and the situations where they occur are discussed. The bias of the first kind is related to the classical Malmquist bias (involving the "volume effect"), while the bias of the second kind appears when standard ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
86
0
3

Year Published

1998
1998
2015
2015

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 102 publications
(89 citation statements)
references
References 73 publications
0
86
0
3
Order By: Relevance
“…The median deviates from the line of the equal distance starting from about 100 pc and this deviation increases toward the larger distances. This trend is in the sense expected from the Malmquist bias of the 2nd kind (Teerikorpi 1997), due to the magnitude limit which at a fixed true distance cuts away stars from the faint side of the luminosity function. (Hill et al 1982) and HIPPARCOS distances for the stars in the NGP area.…”
Section: Distance Estimatesmentioning
confidence: 54%
“…The median deviates from the line of the equal distance starting from about 100 pc and this deviation increases toward the larger distances. This trend is in the sense expected from the Malmquist bias of the 2nd kind (Teerikorpi 1997), due to the magnitude limit which at a fixed true distance cuts away stars from the faint side of the luminosity function. (Hill et al 1982) and HIPPARCOS distances for the stars in the NGP area.…”
Section: Distance Estimatesmentioning
confidence: 54%
“…It is caused to the fact that faint galaxies are missing in the sample because of the limiting apparent magnitude (see the review paper by Teerikorpi 1997). To reach large distances with limited bias, we have to consider only intrinsically bright galaxies.…”
Section: Selection Of Primary Calibratorsmentioning
confidence: 99%
“…Two methods exist to detect unbiased galaxies: the method of normalized distances (Bottinelli et al 1986) and the Spaenhauer diagram (Spaenhauer 1978) used by Sandage (1994). A detailed discussion about these methods is given by Teerikorpi (1997). In the case of galaxies which are sosie of a same calibrator, both diagrams are equivalent.…”
Section: Correction For the Malmquist Biasmentioning
confidence: 99%
“…However, it has been convincingly shown that such deviations from linearity are easily produced by the Malmquist bias in magnitude limited samples [201,202,194] and when one by-passes this problem using suitable methods, the linearity is recovered. The second main advancement is concerned with measurement of the value of the Hubble constant H 0 .…”
Section: Observed Hubble Lawmentioning
confidence: 99%